2017
DOI: 10.1177/0907568217690031
|View full text |Cite
|
Sign up to set email alerts
|

Lives on hold: A qualitative study of young refugees’ resilience strategies

Abstract: Although the literature on positive adjustment following traumatic events is growing, only a few studies have examined this phenomenon in young refugees. Using the social-ecological framework, the aim of this study was to identify factors and processes that according to young refugees promote their resilience. A total of 16 treatment-seeking refugees aged 13–21 years, living in the Netherlands, were interviewed. Data analysis revealed four resilience strategies: (1) acting autonomously, (2) performing at schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…Although IAT recorded a larger treatment effect than CBT in relation to improving resilience at the 6-week follow-up, the changes for both arms were small as were the difference in effects between them. The finding may reflect the lack of specificity of the measure used in relation to the specific focus of the therapy, which, in keeping with the informing model, is focused on the construct of adaptation, or more generally, that the measure used was not wholly congruent with concepts or ways of expressing resilience in the cultures of the participating groups [18,48], noting that the transcultural universality of the concept and/or measurement of resilience remains an issue of contention [49]. In contrast, IAT achieved favourable changes on the majority of scales of the ADAPT-derived measure (noting that the difference for the ASI-3 scale of injustice was equivocal, possibly reflecting the low endorsement of items on this scale).…”
Section: Consideration Of Results In the Context Of The Current Litermentioning
confidence: 99%
“…Although IAT recorded a larger treatment effect than CBT in relation to improving resilience at the 6-week follow-up, the changes for both arms were small as were the difference in effects between them. The finding may reflect the lack of specificity of the measure used in relation to the specific focus of the therapy, which, in keeping with the informing model, is focused on the construct of adaptation, or more generally, that the measure used was not wholly congruent with concepts or ways of expressing resilience in the cultures of the participating groups [18,48], noting that the transcultural universality of the concept and/or measurement of resilience remains an issue of contention [49]. In contrast, IAT achieved favourable changes on the majority of scales of the ADAPT-derived measure (noting that the difference for the ASI-3 scale of injustice was equivocal, possibly reflecting the low endorsement of items on this scale).…”
Section: Consideration Of Results In the Context Of The Current Litermentioning
confidence: 99%
“…Nevertheless, it might be premature to equate growth directly with something positive. A qualitative study among adolescent refugees showed that all youngster perceived growth; they had become stronger and more independent through the hardship they endured, but they did not perceive this as particularly positively because they had lost their childhood (Sleijpen, Mooren, Kleber, & Boeije, 2015 ). These young refugees appeared to have become wiser, but sadder individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this may materialize in the way that they dress or in what language they use. In addition, children and young people may take pride in helping their parents, or might come to feel they have a greater sense of control over their situation through the help they give (Sleijpen et al, 2017).…”
Section: Adjusting To the New Culturementioning
confidence: 99%
“…The role of social support in the resettlement and integration of migrants is widely recognized (Schweitzer et al, 2006;Simich et al 2003;Williams, 2006). For children and young people, social networks and social support are of key importance given their role in facilitating both adjustment to the new society and continuity with the culture of origin (Ní Raghallaigh and Gilligan, 2010;Sleijpen et al, 2017). Indeed, research by Oppedal and Idsoe (2005) shows that social support directly benefits mental health and indirectly strengthens young people's capacity to deal with discrimination.…”
Section: Social Supportmentioning
confidence: 99%